P44 COPD Patients derived benefits from attending PR: 'This has given me my life back'. (16th November 2010) - Matheson, L; O'Connor, J; Cartwright, T; Blunt, CH; Clow, A; Lee, C; Elkin, S
Abstract : Objectives: The effectiveness of Pulmonary Rehabilitation (PR) diminishes over time. Little is known about the role of patients′ beliefs and experiences of PR in the maintenance of outcomes. The aim of this study was to explore COPD patients′ experiences of PR in completers and non-completers. Methods: Purposive sampling was employed to recruit COPD patients referred to an outpatient PR. Participants were interviewed pre (n=15) and post (n=10) PR, approximately 1–2 weeks after the programme. Eight participants completed PR, two dropped out and five were lost to follow-up. Data were analysed using Thematic Analysis. Results: A strong theme to emerge was ' empowerment through attending PR ' as physical improvements derived from PR gave participants a sense of freedom and inspired the motivation to re-engage with life again. Participants regained greater control over the condition, and improvements in mood prompted a renewed sense of optimism and hope for the future. Social re-engagement was often the most highly valued aspect of PR, which provided companionship and normalised the condition. Collectively, positive outcomes inspired determination and ' efforts to maintain the benefits '. Peer support was vital in motivating participants to continue exercise regimes. Potential barriers to maintaining exercise were discussed. ' Improvements to service provision ' were felt necessary to facilitate long-term maintenance, in the form of formalised follow-up sessions and telephone calls. A few had ongoing issues with anxiety, suggesting the need for individual counselling. ' Reasons for drop-out ' included a threatened sense of autonomy and control, negative illness perceptions, inappropriate timing of PR as well as practical and medical issues. These participants were still smokers, and lacked desire for behaviour change. Participants who didn′t attend displayed overwhelming scepticism about PR effectiveness. Conclusions: These findings indicate that immediately following PR, patients feel empowered to continue exercising, due to perceiving multiple benefits. The value placed on peer support demonstrates that this is an important motivator in promoting maintenance. This study highlights COPD patients′ preferences in terms of how service provision aimed at facilitating long-term maintenance of outcomes could be improved, and has implications for the development of psychosocial interventions for patients who are reluctant to attend.